An integrated intuitionistic fuzzy mcdm approach to rank alternatives of polycarbonate thermoplastic resins - ŞENVAR, ÖZLEM; BULKAN, SEROL (My University, 2022)
Polycarbonate (PC) resins are widely preferred by manufacturers to produce a large portfolio of products. It is in the group of thermoplastic polymers. PCs are durable, flame-retardant, and have efficient electricity insulation performance. They can be used to produce many different types of products like capacitors, dome lights, roofing sheets, compact disks, water bottles, decorative bezels, etc. It is a crucial issue to select rational PC resin specific to the application area. The manufacturers can optimize their processes, as well as finances by selecting the most appropriate resin. Many methods may be applied to optimize the selection process. In this paper, a Multi-Criteria Decision-Making (MCDM) Model is proposed that considers both technical criteria and operational criteria. The Intuitionistic Fuzzy Analytical Hierarchy Process (IF-AHP) method is integrated into the Intuitionistic Fuzzy Goal Programming (IF-GP) method to weight criteria, assess the alternatives, and suggest ranking of the alternatives. A sensitivity analysis completes the methodology to determine the boundaries of the solution. The results reveal that they are very sensitive to weighting preferences since PC resin alternatives show very similar properties considering defined criteria.
Keywords: Intuitionistic Fuzzy Set; Analytical Hierarchy Process; Goal Programming; Polycarbonate